The mediating role of corporate image on the retailer’s corporate social responsibility practices and corporate reputation of a fast-food chain company - Chan, Tak Jie; Taher, Surug Saleh; Sharipudin, Mohamad-Noor Salehhuddin; Huam, Hon Tat; Khaw, Thean Boon (Growing Science, 2024)
The purpose of the study is to examine the mediating role of corporate image on the influence of retailers’ corporate social responsibility (CSR) practices of a fast-food chain brand and its corporate reputation. The study utilized the dimensions of the retailer’s CSR dimension. This study focused on the external stakeholders (customers) of X fast food brand in Klang Valley. Social exchange theory was employed to guide the study. Quantitative (survey) methods have been used in this study, whereby 150 valid online questionnaires were gathered among the customers in the Petaling Jaya and analyzed using Partial Least Square Structural Equation Modelling (Smart-PLS 4.0). The findings showed that Philanthropic activities, Respect for the Environment, and Respect for Consumers have positive and significant relationships with corporate image, and corporate image also has a positive and significant relationship with corporate reputation. Furthermore, there is a significant mediating effect of corporate image on the relationship between CSR practices (Respect for Consumers, Respect for the Environment, Philanthropic Activities) and corporate reputation. The conclusion, implications, and suggestions for future studies were also discussed.